1989
DOI: 10.1126/science.2648573
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Versus Actuarial Judgment

Abstract: Professionals are frequently consulted to diagnose and predict human behavior; optimal treatment and planning often hinge on the consultant's judgmental accuracy. The consultant may rely on one of two contrasting approaches to decision-making—the clinical and actuarial methods. Research comparing these two approaches shows the actuarial method to be superior. Factors underlying the greater accuracy of actuarial methods, sources of resistance to the scientific findings, and the benefits of increased reliance on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
1,025
2
32

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,044 publications
(1,083 citation statements)
references
References 37 publications
24
1,025
2
32
Order By: Relevance
“…For more abstract or complex tasks, proceduralization is a term used to define systematic externalized systems for improving decision making (Bazerman, 1998), often with computer assistance (Dawes et al, 1989), which our system does. Computerized displays to assist users in decision making are often domainspecific expert systems (Shortliffe, 1983;Chignell and Peterson, 1988;Schkade and Kleinmuntz, 1994;Stone et al, 1997), whereas our system is domain-general.…”
Section: Augmented Cognition Human-agent Human-robot Human-swarm Imentioning
confidence: 99%
“…For more abstract or complex tasks, proceduralization is a term used to define systematic externalized systems for improving decision making (Bazerman, 1998), often with computer assistance (Dawes et al, 1989), which our system does. Computerized displays to assist users in decision making are often domainspecific expert systems (Shortliffe, 1983;Chignell and Peterson, 1988;Schkade and Kleinmuntz, 1994;Stone et al, 1997), whereas our system is domain-general.…”
Section: Augmented Cognition Human-agent Human-robot Human-swarm Imentioning
confidence: 99%
“…It must be noted that individual patients, rare events and interpretation of patient utility function are not included in statistical methods. Clinicians, therefore, often find exception to actuarial conclusions [22] that cannot compensate for "pattern recognition" focussed by specialisation which in itself constrains cognition [23]. The problem with medical decisions is that the consultant rarely gets immediate feedback about the criteria he or she used in making the judgements.…”
Section: The Patientmentioning
confidence: 99%
“…It is assumed the clinician uses both but if the clinical and actuarial facts do not agree a choice must be made. Research has shown that clinical choices are not as accurate as actuarial evaluation of outcome [22]. It must be noted that individual patients, rare events and interpretation of patient utility function are not included in statistical methods.…”
Section: The Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has consistently demonstrated that actuarial models (e.g., regression or other reasonable mechanical combinations of data) tend consistently to outperform expert judgment in the prediction of human behavior (Dawes, Faust, & Meehl, 1989;Grove & Meehl, 1996;Highhouse, 2008).…”
Section: Clinical Vs Actuarial Judgmentmentioning
confidence: 99%